JUNGIAN CONSCIOUS AND UNCONSCIOUS PSYCHOLOGICAL TYPES OF MEILIN “MEI” LEE IN TURNING RED MOVIE - Putri, Tasya Azura; Nurochman, Nurochman (Journal of Language and Literature, 2023)
Every human has psychological conditions including personality types, and it is said that fictional characters are reflections of actual people. This research aimed to find a fictional character named Meilin “Mei” Lee’s conscious and unconscious personality types. This research used Meilin “Mei” Lee as an object of the research and the Turning Red movie as the source data with its action and dialogues done by the characters as the primary data. To find Meilin “Mei” Lee’s personality types, this research used the psychological types theory proposed by Carl Jung and the qualitative descriptive method to describe the findings. The result showed that out of 8 types, Meilin “Mei” Lee has 7 conscious psychological types with a total of 28 data found within the movie. 3 data of extraverted thinking type, 6 data of introverted thinking type, 2 data of extraverted feeling, 4 data of introverted feeling, 7 data of extraverted sensation type, 3 data of introverted sensation type, 3 data of extraverted intuition type, while the introverted intuition type counts as her unconscious type.